2022
DOI: 10.3389/fcvm.2022.939972
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub biomarkers of myocardial infarction by single-cell sequencing, bioinformatics, and machine learning

Abstract: BackgroundMyocardial infarction (MI) is one of the first cardiovascular diseases endangering human health. Inflammatory response plays a significant role in the pathophysiological process of MI. Messenger RNA (mRNA) has been proven to play a key role in cardiovascular diseases. Single-cell sequencing (SCS) technology is a new technology for high-throughput sequencing analysis of genome, transcriptome, and epigenome at the single-cell level, and it also plays an important role in the diagnosis and treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…They also found that Nobiletin, which targets PLA2G4, may indicate a third pathway for the treatment of acute myeloid leukemia. Zhang [ 90 ] utilized SVM and LASSO to screen the underlying feature biomarkers in four RNA microarray datasets of myocardial infarction. These two machine learning methods yielded 10 and 14 genes, respectively.…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%
“…They also found that Nobiletin, which targets PLA2G4, may indicate a third pathway for the treatment of acute myeloid leukemia. Zhang [ 90 ] utilized SVM and LASSO to screen the underlying feature biomarkers in four RNA microarray datasets of myocardial infarction. These two machine learning methods yielded 10 and 14 genes, respectively.…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%
“…By examining individual cells, particularly their gene expression patterns within different cell subpopulations, researchers have successfully identified a range of potential biomarkers associated with MI. For example, Zhang et al ( 280 ) used scRNA-seq technology to reveal the potential roles that IL1B and TLR2 may play in the diagnosis of MI, which are closely related to various infiltrating immune cells. Another study also identified a series of immune cell-related genes, including FOS , DUSP1 , CXCL8 , and NFKBIA , which can not only differentiate between AMI and coronary heart disease (CHD) but also predict the risk of HF in AMI patients ( 281 ).…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…However, AMI patients need to complete continuous follow-ups to evaluate and improve their prognosis. Recently, the Gensini score and the SYNTAX score were used to predict the prognosis of AMI in clinics, but they could not be widely applied due to their complexity [ 3 5 ]. It was estimated that more than 50% of malnourished critically ill AMI patients admitted to the intensive care unit (ICU) could have more comorbidities and the risk of organ dysfunction [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%